2005
DOI: 10.1161/circulationaha.104.502179
|View full text |Cite
|
Sign up to set email alerts
|

External Beam Radiation to Prevent Restenosis After Superficial Femoral Artery Balloon Angioplasty

Abstract: Background— Femoropopliteal percutaneous transluminal angioplasty (PTA) remains limited by restenosis. Although vascular brachytherapy may be effective in reducing restenosis, external beam radiation would be more practical to administer after PTA. Methods and Results— After femoropopliteal PTA without stent placement, 99 patients were randomly assigned to 0 Gy (placebo; n=24), 7 Gy (n=24), 10.5 Gy (n=26), or 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…At 1-year follow-up, there was a significant benefit for the group treated with 14 Gy in a single treatment session compared with the control and lower-dose groups. 62 The late catch-up phenomenon demonstrated for endovascular brachytherapy suggests that a longer follow-up will be necessary to determine the benefit for external-beam radiation to prevent restenosis. There are no intravascular brachytherapy delivery devices available in the United States to treat 5-to 6-mm-diameter SFA vessels.…”
Section: White and Gray Endovascular Therapies For Padmentioning
confidence: 99%
“…At 1-year follow-up, there was a significant benefit for the group treated with 14 Gy in a single treatment session compared with the control and lower-dose groups. 62 The late catch-up phenomenon demonstrated for endovascular brachytherapy suggests that a longer follow-up will be necessary to determine the benefit for external-beam radiation to prevent restenosis. There are no intravascular brachytherapy delivery devices available in the United States to treat 5-to 6-mm-diameter SFA vessels.…”
Section: White and Gray Endovascular Therapies For Padmentioning
confidence: 99%
“…Forty RCTs were accepted into the narrative review, published in 61 references. Study characteristics are shown in Table S1 (supporting information). Most of the trials recruited participants who had angioplasty of the superficial femoral and/or popliteal artery.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, other forms of radiation therapy -other than the beta-irradiation we studied -may show utility in the future. For instance, external beam radiation was reported as promising for femoral artery lesions [46]. Drug eluting stents (also an antiproliferative therapy) may limit the necessity for brachytherapy in the future for several reasons.…”
Section: Discussionmentioning
confidence: 99%